Effect of Spiritual Leadership to Organizational Culture and Employee’s Loyalty - Arasy Alimudin; Dahlia Septian; Agus Dwi Sasono; Ani Wulandari (STKIP Singkawang, 2017)
Although the leader of the Society’s Eye Hospital, East Java has the characteristics of spiritual leadership as in the dimensions of spiritual leadership developed by Fry (2003) including vision, hope / faith, and altruistic love, however the level of employee turn over is still high. To address this problem, the research is using a quantitative causality approach and SEM PLS model as the data analysis technique used. The result of the research shows that there is a significant positive influence on spiritual leadership towards the organizational culture. A significant positive influence of organizational culture also seen on employee’s loyalty, and there is a positive but insignificant influence of spiritual leadership on employee’s loyalty.